Present and Future Ways of Physical Property Protection - Lovecek, Tomas (Communications - Scientific letters of the University of Zilina, 2008)
Nowadays in the territory of Slovak republic, the property protection and security systems design lies in realization of requirements following from security requirements specifying details of tangible property protection (Law, Risk Analyze, Internal regulations of the company). In this article, three basic approaches to secure physical protection of property will be introduced. There is directive-oriented, variant-oriented and variable way of physical protection. For the most effective way of protection we can consider the variable way of protection, which allows due to its flexibility designing of the system in such a way, that it best suits requirements, conditions and possibilities of the subject.